2017
DOI: 10.1159/000479972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intentional Weight Loss on Markers of Oxidative Stress, DNA Repair and Telomere Length - a Systematic Review

Abstract: Background: Altered levels of markers of oxidative stress, DNA repair, and telomere integrity have been detected in obese individuals and may underlie the pathogenesis of obesity-related diseases. However, whether or not such effects are reversed by intentional weight loss has not been systematically reviewed. Methods: A literature search in PubMed/Medline identified 2,388 articles of which 21 studies (randomized controlled trial (RCT) (n = 10) and non-randomized intervention studies (n = 11)) were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Therefore, it is conceivable that the reduced activity of this repair system is causally related to oxidation of DNA bases in obese animals. Himbert et al . evaluated the literature regarding effects of weight loss on DNA repair functions and telomere lengths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is conceivable that the reduced activity of this repair system is causally related to oxidation of DNA bases in obese animals. Himbert et al . evaluated the literature regarding effects of weight loss on DNA repair functions and telomere lengths.…”
Section: Discussionmentioning
confidence: 99%
“…[44] Furthermore, a number of human investigations were published recently indicating that weight loss reduces obesity associated oxidative stress (for details see ref. [45]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in obese patients, reduced energy intake and associated body weight loss was reported to reduce DNA damage [ 68 ]. However, a recently published systemic review showed the inconsistent effects of weight loss on telomere length and DNA repair [ 69 ]. Therefore, further studies are needed to establish the effect of weight loss on DNA damage and DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…In all of them telomere length was determined in either leukocytes or PBMC before and after the intervention. However, although the type of interventions described are known to impinge on oxidative-stress responses [78][79][80][81][82], only a few related telomere length measurements to changes in oxidative stressrelated parameters [62,64,65]. A brief description of these studies is summarized below.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%